1953
DOI: 10.1161/01.cir.8.6.801
|View full text |Cite
|
Sign up to set email alerts
|

The Electrocardiographic Pattern of Hypopotassemia with and without Hypocalcemia

Abstract: Detailed analysis of the electrocardiogram in patients with hypopotassemia without hypocalcemia showed that the Q-U interval and its components (Q-oT, Q-aT, Q-T, and Q-aU) have essentially the same duration as in normal subjects for the same heart rate and sex. The typical hypopotassemia pattern is characterized by progressive depression of S-T, lowering and inversion of T and increase of U in left precordial leads. In hypopotassemia with hypocalcemia S-T and Q-T, but not Q-U, are prolonged, causing an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

1954
1954
2001
2001

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…All these factors may have played a role in the development of hypokalemia in our patients. Arrhythmias, including ventricular extrasystoles and ventricular bigeminy, have been consistently observed by Surawicz and Lepeschkin [16] when the potassium values are below 2.6 meq./l, and disappear after administration of potassium. Weaver and liurcheU found extrasystoles with a potassium below 3.6 meq./l in 24% of normotensive and in 30% of hypertensive pa tients [18].…”
Section: Discussionmentioning
confidence: 59%
“…All these factors may have played a role in the development of hypokalemia in our patients. Arrhythmias, including ventricular extrasystoles and ventricular bigeminy, have been consistently observed by Surawicz and Lepeschkin [16] when the potassium values are below 2.6 meq./l, and disappear after administration of potassium. Weaver and liurcheU found extrasystoles with a potassium below 3.6 meq./l in 24% of normotensive and in 30% of hypertensive pa tients [18].…”
Section: Discussionmentioning
confidence: 59%
“…14 In 1953, Surawicz and Lepeschkin described a series of patients with hypokalemia and frequent junctional and ventricular premature beats; in all cases the arrhythmias disappeared with administration of potassium. 15 Gettes et al used a microelectrode technique to show that perfusion of low potassium solutions resulted in ventricular ectopic beats, ventricular tachycardia, and ventricular fibrillation. 16 Several clinical studies have demonstrated that an increased incidence of ventricular arrhythmias is associated with the hypokalemia induced by diuretic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The same sequence was observed recently in rabbit hearts perfused with a low potassium solution.25 On the other hand, potassium decreases the U waves and the afterpotentials, and suppresses all coupled extrasystoles. 23 In acidosis, which is known to elevate the U waves, a supernormal phase was found to appear in the mammalian heart, and this was accompanied by the appearance of ventricular extrasystoles with coupling intervals corresponding to the duration of this phase. 19 Slowing of the heart rate, which tends to elevate the U waves, also favors the appearance of coupled rhythms; we have seen this event in many cases of atrial fibrillation treated with digitalis, where coupled extrasystoles were precipitated only by ventricular complexes appearing after long pauses.…”
Section: Discussionmentioning
confidence: 99%